Protocolo de Prevención de Caídas A Nivel y Desnivel en una Institución de Educación Superior - Ardila Rodríguez, Juan David; Huelgos Urrego, Luis Carlos (Universidad Antonio Nariño, 2023)
According to data from the World Health Organization (WHO), there are 37.3 million falls each year in the world, of which medical attention is required due to their severity, with level and uneven falls being one of the major causes. of occupational accidents in the country and in the same way another series of cultural conditions, age or other reasons that can lead to increased risk are associated.